IMPLEMENTATION OF WAYFINDING SIGN IN THE ACCESSIBILITY OF SOFTBALL STADIUM IN SURABAYA - Putra, Heristama; Hastorahmanto, Prabani (Border: Jurnal Arsitektur, 2024)
A stadium typically consists of one or more large-scale building masses designed to accommodate significant numbers of visitors such as spectators, administrators, and athletes. With a large number of visitors, it needs careful planning of land use due to the extensive area required for stadium construction. Efficient movement within the building is essential, particularly in guiding visitors between spaces. The design for the Surabaya softball stadium spans four floors and occupies a substantial land area. However, a key challenge lies in addressing visitor confusion, especially among spectators, regarding access to different spaces. To mitigate this, effective identification systems, such as signage, are crucial for facilitating navigation within the stadium. The implementation of wayfinding signage serves as a solution to direct users to their desired locations, ensuring smooth movement throughout the facility. Additionally, the organization of space and zoning by function, supported by clear markers, helps prevent cross circulation. Unregulated circulation may lead to congestion at specific points if adequate signage and space designation are lacking. Therefore, providing clear names and directional instructions through wayfinding signs is vital to enhance spatial accessibility and streamline visitor movement within the stadium.